Investigating the Mediating Role of Reflective Identity in the Relationship between Neuroeconomics and Entrepreneurial Decision-Making - Farshid Khajehmahmood; Aleme Keikha; Mehdi Zivdar (International Journal of Business and Development Studies)
The present study aims to investigate the mediating role of reflective identity in the relationship between neuroeconomics and entrepreneurial decision-making . The research method is applied in terms of purpose and descriptive survey based on structural equation modeling in terms of nature and procedure. A questionnaire was used to collect field data. The face and content validity of the questionnaire was confirmed by experts and the construct validity was calculated using confirmatory factor analysis. The reliability of the research tools was calculated using Cranach’s alpha test and a composite reliability higher than 0.7 was achieved, which reveals the appropriate validity of the research tools. The statistical population of the research consists of 110 entrepreneurs based in the Science and Technology Park of Zahedan. Morgan's table was applied to determine the sample size, and 86 individuals were selected as the statistical sample by using simple randomization. For analyzing the research data and answering the research hypotheses, SPSS23 and Smart PLS software and the structural equation modeling test were used. The research findings indicated that reflective identity has a mediating role in the relationship between neuroeconomics and entrepreneurial decision-making of the entrepreneurs based in the Zahedan Science and Technology Park. It should be mentioned that a better understanding of the issues pertaining to the upcoming choices for entrepreneurs will lead to better decisions. Therefore, this understanding of the neural basis of decision-making can lead to entrepreneurial decision-making in a special way, which often includes risky choices under conditions of uncertainty.